(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2023)
The primary objective of this study was to analyze the level of parents’ satisfaction with the behaviour and roles of office staffs, receptionists, and roles of teachers. This study has applied the quantitative approach along with the survey method. The survey instrument was used to collect two hundred (N =200) data from the parents of Montessori schools in Gaindakot 1 and 2, Nawalpur. Random sampling was used to select the parents of Montessori schools. The results show positive association between the behaviour and roles of office staff, receptionists, and parents, satisfaction. Similarly, the results show a negative association between the facilities of Montessori schools, the influence of Montessori quality and behaviour and the roles of Montessori teachers. This study has concluded that there was an association between the quality of Montessori education and parental satisfaction. This study’s implications would benefit new researchers, scholars, colleges, local government, Montessori schools, school administrators and owners and investors of private schools in Nepal.